Atypical Chemokine Receptors and Their Roles in the Resolution of the Inflammatory Response - Bonecchi, Raffaella; Graham, Gerard J. (Frontiers in Immunology, 2016)
Chemokines and their receptors are key mediators of the inflammatory process regulating leukocyte extravasation and directional migration into inflamed and infected tissues. The control of chemokine availability within inflamed tissues is necessary to attain a resolving environment and when this fails chronic inflammation ensues. Accordingly, vertebrates have adopted a number of mechanisms for removing chemokines from inflamed sites to help precipitate resolution. Over the past 15 years it has become apparent that essential players in this process are the members of the atypical chemokine receptor family. Broadly speaking this family is expressed on stromal cell types and scavenges chemokines to either limit their spatial availability or to remove them from in vivo sites. Here we provide a brief review of these atypical chemokine receptors and discuss their involvement in the resolution of inflammatory responses and the therapeutic implications of our current knowledge.